Structure and physical mechanical properties of multicomponent (Ti-Zr-Cr-Nb)N coatings’ obtained by vacuum-arc deposition - Yeskermessov, D.K.; Plotnikov, S.V. (Recent Contributions to Physics, 2017)
In the article discusses the results of the deposition of nanostructured coatings obtained by vacuum arc deposition of cathode (Ti-Zr-Cr-Nb), and analyzes their structure, morphology, elemental composition, and tribological properties (friction, wear and adhesion). Investigated multicomponent coating nitride (Ti-Zr-Cr-Nb)N in this study were obtained using a well-developed technique of vacuum-arc deposition. Theoretical and experimental studies show that the chemical composition, microstructure and mechanical properties of coatings are based closely on deposition parameters (the working gas pressure and bias potential on the substrate). The microstructure and mechanical properties (Ti-Zr-Cr-Nb)N coatings were investigated using a scanning electron microscope (SEM) equipped with energy dispersive microanalysis prefix and X-ray diffraction (XRD). Phase analysis nitride coatings (Zr-Ti-Cr-Nb) N indicates a TiN phase, NbTiN2, ZrTiNb, ZrNb, TiCr and α-Ti. The coating thickness reached 6.8 µm and their maximum of hardness was H = 43,7 GPa. Tribological (test «ball-on-disc») and mechanical (scratch test) properties of multi-coating were studied. The experimental results obtained by studying multicomponent (Ti-Zr-Cr-Nb) N coatings’ are promising and can be used as protective coatings for cutting tools and structural materials.